2009
DOI: 10.1007/s10616-009-9199-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment and concentration of fish serum on cell growth in adhesion culture of Chinese hamster ovary cells

Abstract: The effects of heat treatment and concentration of fish serum (FS) on cell growth and human granulocyte-macrophage colony-stimulating factor (hGM-CSF) production in an adhesion culture of recombinant Chinese hamster ovary (CHO) cells, DR1000L4N, were investigated. The addition of heat treated FS instead of non-heat-treated FS improved cell growth in terms of cell density, which reached 60% that in 10% fetal calf serum (FCS)-containing medium (FCS medium). A decrease in FS concentration from 10 to 1.25% markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Several groups already demonstrated that differences in serum concentration or type could highly affect cell adhesion (Fujiwara et al, 2009;Grinnell and Feld, 1979;Schmidt et al, 2011). Our study confi rmed that serum greatly affects cell adhesion in addition to surface patterning.…”
Section: Wwwecmjournalorg E Lamers Et Al Dynamic Cell Adhesion Andsupporting
confidence: 81%
“…Several groups already demonstrated that differences in serum concentration or type could highly affect cell adhesion (Fujiwara et al, 2009;Grinnell and Feld, 1979;Schmidt et al, 2011). Our study confi rmed that serum greatly affects cell adhesion in addition to surface patterning.…”
Section: Wwwecmjournalorg E Lamers Et Al Dynamic Cell Adhesion Andsupporting
confidence: 81%
“…The cell-growth-stimulating activity of fish serum for MSCs is yet unclear, although the use of fish serum has been investigated (Fujiwara et al 2007(Fujiwara et al , 2009(Fujiwara et al , 2010. The in vitro cell-growth-stimulating activity of adult human serum was much lower than that of fetal serum.…”
mentioning
confidence: 99%
“…The released cells were mix of plenty of myoblasts and fibroblasts, and the external characteristics of both types of cells were so similar that they cannot be distinguished and well separated by their external characteristics. However, the fibroblasts could adhere on some plastic surface more easily than the myoblasts did (Fujiwara et al 2009). Thus, we obtained plenty of duck myoblasts with high purity by using the differential attachment technique.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation and differentiation of myoblasts can be influenced by the choice of the serum concentration in the culture medium. Low concentration of serum in culture medium can induce cell differentiation, whereas high concentration serum can lead to a proliferation tendency of the cells (Fujiwara et al 2009). In this study, we added serum with a concentration of 15% to the culture medium, resulting in a longer proliferation phase for the duck myoblasts.…”
Section: Discussionmentioning
confidence: 99%